2015
DOI: 10.1007/s10571-015-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Apoptosis of Astrocytes: Therapeutic Intervention by Minocycline

Abstract: Astrocytes are most abundant glial cell type in the brain and play a main defensive role in central nervous system against glutamate-induced toxicity by virtue of numerous transporters residing in their membranes and an astrocyte-specific enzyme glutamine synthetase (GS). In view of that, a dysregulation in the astrocytic activity following an insult may result in glutamate-mediated toxicity accompanied with astrocyte and microglial activation. The present study suggests that the lipopolysaccharide (LPS)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 75 publications
3
20
0
Order By: Relevance
“…To confirm the inflammatory response induced by LPS, we carried out histological analysis of animals at each timepoint studied by HP 13 C MRS. Iba1 and GFAP staining confirmed a substantial increase in microglia/macrophages and astrocytes at 7 days following LPS injection, respectively (compared with both 7‐day contralateral data and baseline/3‐day ipsilateral data). This result was in line with several previous studies; Go et al demonstrated a significant increase in microglia at 7 days following an intrahippocampal LPS injection, and Sharma et al showed a similar increase, this time following an intracerebroventricular injection, and additionally observed an increase in GFAP‐positive astrocytes. Future studies could clarify the homogeneity and extent of the LPS response throughout the brain relative to the injection site.…”
Section: Discussionsupporting
confidence: 93%
“…To confirm the inflammatory response induced by LPS, we carried out histological analysis of animals at each timepoint studied by HP 13 C MRS. Iba1 and GFAP staining confirmed a substantial increase in microglia/macrophages and astrocytes at 7 days following LPS injection, respectively (compared with both 7‐day contralateral data and baseline/3‐day ipsilateral data). This result was in line with several previous studies; Go et al demonstrated a significant increase in microglia at 7 days following an intrahippocampal LPS injection, and Sharma et al showed a similar increase, this time following an intracerebroventricular injection, and additionally observed an increase in GFAP‐positive astrocytes. Future studies could clarify the homogeneity and extent of the LPS response throughout the brain relative to the injection site.…”
Section: Discussionsupporting
confidence: 93%
“…To confirm the inflammatory response induced by LPS, we carried out histological analysis of animals at each timepoint studied by HP 13 C MRS. Iba1 and GFAP staining confirmed a substantial increase in microglia/macrophages and astrocytes at 7 days following LPS injection, respectively (compared to both 7 day contralateral data and baseline/3 day ipsilateral data). This result was in line with several previous studies 1,2,7,8,37,38 ; Go et al 7 demonstrated a significant increase in microglia at 7 days following an intrahippocampal LPS injection, and Sharma et al 38 showed a similar increase, this time following an intracerebroventricular injection, and additionally observed an increase in GFAP-positive astrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Prolonged over-expression of pro-inflammatory cytokines has been extensively reported to cause neuronal loss [12,13,17,[26][27][28] . The present study makes a novel attempt to answer the questions concerning the long-term impact of early life bacterial infection on myelination and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), an endotoxin of gram-negative bacteria has the potential to activate innate immune response in a host by binding to the toll-like receptor-4 [11] . It activates the glial cells, that is, astrocytes and microglia and upregulates the release of a cascade of pro-inflammatory cytokines and interleukins such as tumor necrosis factor, interleukin-1β, and interferon gamma [12,13] . Both developing and mature neurons and glia possess numerous pro-inflammatory cytokine receptors, which make them susceptible to inflammation-assocaited damage [14] .…”
mentioning
confidence: 99%